Numerical simulation of the heat conduction in electrical cables - Čiegis, Raimondas; Ilgevičius, Audrius; Liess, Heinz; Meilūnas, Mečislavas; Suboč, Olga (Mathematical Modelling and Analysis, 2007)
The modelling of the heat conduction in electrical cables is a complex mathematical problem. To get a quantitative description of the thermo‐electrical characteristics in the electrical cables, one requires a mathematical model for it. It must involve the different physical phenomena occurring in the electrical cables, i.e. heat conduction, convection and radiation effects, description of heat sources due to current transitions. Since the space in mobile systems is limited and weight is always reduced, wire conductor sizes must be kept as small as possible. Thus the main aim is to determine optimal conductor cross‐sections for long standing loads. In this paper we develop and validate a set of mathematical models and numerical algorithms for the heat transfer simulation in cable bundles. The numerical algorithms are targeted to the two‐dimensional transient heat transfer mathematical models. Finally, a validation procedure for the coefficient validation of the differential equations is carried out. Results of numerical experiments are presented.First Published Online: 14 Oct 2010